New Records of Lepidoptera from the Kola Peninsula, Northwestern Russia - Kozlov, Mikhail; Jalava, Jukka; Shutova, Elena (Entomologica Fennica, 2000)
We report 91 species of Lepidoptera discovered from the Kola Peninsula for the first time and confirm records of 15 species from which our earlier information was based solely on the literature. Tinea svenssoni Opheim, 1965, Biselachista kebneella Traugott-Olsen & Nielsen, 1977 and Apotomis fraterculana Krogerus, 1945 are reported for the first time from Russia. The Lepidopteran fauna of the Kola Peninsula now numbers 676 species.